PTU-170 Fibulin-5 expression in the skin of patients with rectal prolapse. (22nd June 2015) - Joshi, HM; Lindsey, I; Cunningham, C; Urban, J; Jones, O
Abstract : Introduction: Rectal prolapse is a prevalent disorder affecting up to 10% of patients in the United Kingdom. Components of the connective tissue other than collagen have been found to be involved in development of prolapse. Elastic fibre organisation differs between controls and subsets of patients with rectal prolapse. Transgenic mice have demonstrated the importance of elastic fibres for maintaining structural and functional integrity of the pelvic floor. Elastic fibres assembly is a complex process and fibulin-5 integral in this process. Mice with null mutation in fibulin-5 ( Fbln5 ¡ / ¡) develop a prolapse that is remarkably similar to that of primates. Method: Between January 2013 and February 2014, skin specimens were obtained prospectively during surgery from 20 patients with rectal prolapse and from 21 patients without prolapse undergoing surgery for other indications. Fibroblasts from the skin were cultured and levels of Fibulin -5 expression was determined on cultured fibroblasts, isolated from these specimens by Quantitative Real-Time PCR. Immunohistochemistry was performed on fixed tissue specimens to assess FIB-5 expression. Results: FIB-5 mRNA expression and FIB-5 staining intensity was significantly lower in the young male patients with rectal prolapse when compared to age matched control groups. (FIB-5 mean +/- SD mRNA relative units) 1.1 +/- 0.41 vs. 0.53 +/- 0.22, p = 0.001] and Intensity score, median (range), 2 (0–3) vs. 1 (0–3), p = 0.05]. There was no significant differences in expression of FIB-5 in women with rectal prolapse compared with control. Conclusion: FIB-5 maybe implicated in the aetiology of rectal prolapse in a subgroup of young male patients. Disclosure of interest: None Declared.